Morality- and norm-based subgroups of disability-sport athletes fiffer on their anticipated guilt and intentions toward doping - Harris, T. S.; Smith, A. L.; Boardley, I. (Adapted Physical Activity Quarterly, 2024)
The purpose of this study was to examine whether subgroups of disability-sport athletes exist on morality- and norm-based doping cognitions and whether these groups differ in anticipated guilt or doping intentions. A survey was completed by 186 athletes (Mage = 37.5 years, 78.0% male, 45.1% wheelchair basketball) assessing norms, doping moral disengagement, anticipated guilt, and intentions to dope. Cluster analysis revealed four distinct subgroups of athletes, including one potentially high-risk subgroup characterized by relatively high scores on doping moral disengagement, subjective norms, and descriptive norms. One-way analysis of variance revealed significantly lower anticipated guilt in two athlete subgroups characterized by relatively higher doping moral disengagement than the other two subgroups. Moreover, the potentially high-risk group had a greater proportion of athletes showing some presence of intention to dope. This study suggests there is a small subgroup of disability-sport athletes at elevated risk of doping who might benefit from targeted antidoping interventions.